Front Cover: Nanomaterials‐assisted metabolic analysis toward in vitro diagnostics (EXP2 3/2022). Issue 3 (17th June 2022) - Yang, Jing; Huang, Lin; Qian, Kun
Abstract : Nanomaterials play an indispensable role in metabolic analysis when integrated with analytical implementations, including electrochemical, optical, and mass spectrometric tools. Nanomaterials‐assisted metabolic analysis characterizes the downstream metabolites and offers real‐time feedback of the human body. It serves as the primary choice to facilitate the in‐vitro diagnostics for indicating the disease condition and guiding the therapeutic decision.